Luteolin suppresses epithelial-mesenchymal transition and migration of triple-negative breast cancer cells by inhibiting YAP/TAZ activity - Cao, Dai; Zhu, Guo-Yuan; Lu, Yan; Yang, Aiping; Chen, Die; Huang, Hui-Jie; Peng, Shu-Xian; Chen, Li-Wen; Li, Ying-Wei (Biomedicine & pharmacotherapy, 2020)
Triple-negative breast cancer (TNBC) is a highly lethal subtype of breast cancer associated with early relapse and metastasis. Epithelial to mesenchymal transition (EMT) plays pivotal roles in the progression of TNBC, including inducing cancer stem cell (CSC) properties, chemoresistance, tumor metastasis, and recurrence. Abnormally activated YAP/TAZ induces EMT in TNBC, making it a promising target for drug development. Our goal is to identify potential YAP/TAZ inhibitors from naturally derivative molecules and further study its effects on inhibiting EMT and metastasis of TNBC. In the current study, we demonstrate that luteolin significantly inhibits YAP/TAZ activity by promoting YAP/TAZ degradation in TNBC cells. Luteolin treatment leads to a decrease of mesenchymal markers and an increase of epithelial markers in both TNBC cells and TAZ-induced mesenchymal cells. Consistently, luteolin treatment inhibits cell migration in TNBC cells. Additionally, luteolin inhibits tumor growth in mice xenografted with TNBC cells. Collectively, our results support luteolin as a novel YAP/TAZ inhibitor for development as a new agent for the treatment of TNBC.